The rapid effects of budesonide plus formoterol in patients with obstructive airway diseases - Bayiz, Hulya (Drug Des Devel Ther, 2015)
INTRODUCTION: The use of a combination inhaler containing budesonide and formoterol (BUD/FOR) to both maintenance and quick relief therapy has been recommended as an improved method of using inhaled corticosteroid/long-acting β agonist therapy. The aim of this study was to investigate the acute effects of BUD/FOR and testing the availability of BUD/FOR for early reversibility test in patients with airway obstruction. PATIENTS AND METHODS: The study was conducted on patients who were admitted to the Department of Pulmonary Medicine, Samsun Medical Park Hospital, Samsun, Turkey. RESULTS: A total of 44 patients were included in the study. The mean age of patients was 48.5±17.3 (range 10–75) years and the male-to-female ratio was 36:8. The pre-bronchodilator pulmonary function test results are as follows: the mean forced vital capacity, 3,025±1,162 mL (76.3%±23.2%); mean forced expiratory volume in 1 second (FEV(1)), 1,898±725 mL (59.2%±19.1%); mean FEV(1)/forced vital capacity, 62.8±6.3% (range 42%–70%); mean peak expiratory flow, 3,859±1,779 mL (48.0%±19.7%); and forced expiratory flow 25%–75%, 1,295±486 mL (35.8%±12.3%). The reversibility was positive in 26 (59.1%) patients. The absolute change and percentage of change in FEV(1) were 318±228 mL and 17.7%±11.9%, respectively. The patients were divided into two groups according to reversibility (reversible and irreversible) and both groups were compared with changes according to spirometric results. FEV(1) values were statistically different between the two groups. CONCLUSION: The fixed combination of BUD/FOR has rapid bronchodilator effect, and they can be used for early reversibility test.